The Role of the Sabhara Patrol Unit in Preventing the Crime of Theft in the Legal Territory of the Kerinci Police - Muhammad Holid Azhari (Indonesian Journal of Police Studies, 2021)
This research is motivated by the high number of criminal acts of theft, be it ordinary theft, stealing, stealing, and robbery. The Kerinci Police took action to prevent the crime of theft by carrying out patrol activities carried out by the Sabhara Unit as the spearhead to prevent the theft. This study aims to describe the role of the sabhara unit patrol in preventing the crime of theft, and the factors that influence the implementation of the Kerinci sabhara unit patrol. This study uses a qualitative approach as well as data collection techniques with interviews, observations, and document studies. From this research, it can be seen a real picture of the prevention efforts carried out by the Kerinci Sabhara Police unit against the crime of theft. To process the data obtained, the researcher uses management theory and crime prevention theory, the concept of patrol, the concept of sabhara, the concept of the crime of theft and preventive measures. The results of the study found that the role of the Sabhara patrol unit had not been fulfilled optimally in accordance with Perkabaharkam Number 1 of 2017 concerning Patrols, because there were internal and external factors that hindered the implementation of the patrol, namely the lack of patrol member personnel, the number of members who did not participate in the Sabhara Dikjur, lack of facilities. infrastructure and the community have not played an active role in helping provide information to patrol officers. Based on the results of the study, the authors suggest the need for patrolling in accordance with SOPs, increasing the intensity of patrolling, increasing the number of personnel and personnel capabilities through the activities of the Dikjur Sabhara and adding facilities and infrastructure. Thus the role of the patrol unit of the Kerinci Sabhara Police in preventing the crime of theft can be fulfilled optimally.